Islamic finance and net zero: the need for sustainability taxonomies - Mohd Thas Thaker, Hassanudin; Hesary, Farhad Taghizadeh (Climate Finance Asia, 2025)
As climate extremes intensify, mobilizing new sources of sustainable finance is urgent. With the Islamic finance industry projected to reach USD 9.75 trillion by 2029, it can play a vital role in closing the climate finance gap. This policy brief highlights the importance of developing unified sustainability taxonomies across Islamic countries to ensure consistency, transparency, and investor confidence. Clear frameworks will enable Green Sukuk and other instruments to better support the transition to a low-carbon, resilient future.